2017
DOI: 10.1108/pijpsm-07-2016-0114
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice and officer “buy in” in American policing

Abstract: Purpose The purpose of this paper is to explore the dimensions of organizational justice in police organizations and evaluate how they contribute to organizational commitment, job satisfaction and compliance with agency rules. Design/methodology/approach A survey of 15,236 sworn officers from a national sample of 88 agencies was used, as well as other agency- and community-level variables. Multi-level models assessed how four dimensions of organizational justice affected these outcomes. Findings More favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 16 publications
3
45
0
1
Order By: Relevance
“…One approach to getting officers to feel more ownership and "buy-in" to new directions is for top management to support and model the types of organizational-justice-related behaviors that are important to employees, including those that are seen as prioritizing interpersonal relations between employees and managers, giving officers a voice, and protecting them from unfair attacks (Rosenbaum & McCarty, 2017). These steps are essential to help minimize feelings of burnout as officers are expected to continue doing police work under the current conditions of extreme mistrust and scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to getting officers to feel more ownership and "buy-in" to new directions is for top management to support and model the types of organizational-justice-related behaviors that are important to employees, including those that are seen as prioritizing interpersonal relations between employees and managers, giving officers a voice, and protecting them from unfair attacks (Rosenbaum & McCarty, 2017). These steps are essential to help minimize feelings of burnout as officers are expected to continue doing police work under the current conditions of extreme mistrust and scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous organizational justice studies have appeared in criminology and criminal justice journals over the past few decades, and their results have shown that police officers, for example, who feel they have been treated fairly by their supervisors report more commitment to their agency's goals, more identification with their agency, and less cynicism toward their job or citizens compared with their counterparts who perceive less organizational justice from their supervisors (Bradford & Quinton, 2014; Bradford, Quinton, Myhill, & Porter, 2014; Donner, Maskaly, Fridell, & Jennings, 2015; Myhill & Bradford, 2013; Rosenbaum & McCarty, 2017; Trinkner, Tyler, & Goff, 2016). What is more, officers who experience fair supervisory treatment report greater job satisfaction and more trust in their agencies (Donner et al., 2015; Wolfe & Nix, 2017).…”
Section: Organizational Justice Among Criminal Justice Employeesmentioning
confidence: 99%
“…Police officers are a group particularly vulnerable to psychopathological disturbances, which leads them to suffer from burnout and affects their quality of life [ 21 , 27 ]. Previous studies show that police officers involved in life-threatening situations, extreme violence, critical incidents, shootings, hostage or negotiation situations, intense exposure to crime scenes, or coworkers’ death or suicide, can develop burnout syndrome associated with mental health problems [ 5 , 24 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%